PREDICTION OF SEXUAL DEVELOPMENT DELAY BY DERMATOGLYPHIC MARKERS IN BOYS - SulimaТ.N.; Bagatskaya, N.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
Dermatoglyphic markers, which permit to predict illness development at pre-clinical stage, have been revealed on the basis of medicogenetic examination of 260 adolescent boys with sexual development delay (SDD) and 90 healthy boys. The algorithm for detection of persons with high risk of sexual development delay occurrence has been given.